Workforce, Workload, and Burnout Among Intensivists and Advanced Practice Providers: A Narrative Review. Issue 4 (April 2019) - Pastores, Stephen M.; Kvetan, Vladimir; Coopersmith, Craig M.; Farmer, J. Christopher; Sessler, Curtis; Christman, John W.; D'Agostino, Rhonda; Diaz-Gomez, Jose; Gregg, Sara R.; Khan, Roozehra A.; Kapu, April N.; Masur, Henry; et al.
Abstract : Objectives: To assess—by literature review and expert consensus—workforce, workload, and burnout considerations among intensivists and advanced practice providers. Design: Data were synthesized from monthly expert consensus and literature review. Setting: Workforce and Workload section workgroup of the Academic Leaders in Critical Care Medicine Task Force. Measurements and Main Results: Multidisciplinary care teams led by intensivists are an essential component of critical care delivery. Advanced practice providers (nurse practitioners and physician assistants) are progressively being integrated into ICU practice models. The ever-increasing number of patients with complex, life-threatening diseases, concentration of ICU beds in few centralized hospitals, expansion of specialty ICU services, and desire for 24/7 availability have contributed to growing intensivist staffing concerns. Such staffing challenges may negatively impact practitioner wellness, team perception of care quality, time available for teaching, and length of stay when the patient to intensivist ratio is greater than or equal to 15. Enhanced team communication and reduction of practice variation are important factors for improved patient outcomes. A diverse workforce adds value and enrichment to the overall work environment. Formal succession planning for ICU leaders is crucial to the success of critical care organizations. Implementation of a continuous 24/7 ICU coverage care model in high-acuity, high-volume centers should be based on patient-centered outcomes. High levels of burnout syndrome are common among intensivists. Prospective analyses of interventions to decrease burnout within the ICU setting are limited. However, organizational interventions are felt to be more effective than those directed at individuals. Conclusions: Critical care workforce and staffing models are myriad and based on several factors including local culture and resources, ICU organization, and strategies to reduce burden on the ICU provider workforce. Prospective studies to assess and avoid the burnout syndrome among intensivists and advanced practice providers are needed.